Relative abundaces of diatom groups and particle fluxes from mooring site CBeu (Cape Blanc) - Oscar E Romero; Gerhard Fischer (PANGAEA, 2020)
A multiannual, continuous sediment trap experiment was conducted at the mooring site CBeu (Cape Blanc eu- trophic, ca. 20 °N, ca. 18 °W; trap depth = 1256-1296 m) in the high-productive Mauritanian coastal upwelling. Here we present fluxes and the species-specific composition of the diatom assemblage, and fluxes of biogenic silica (BSi, opal) and total organic carbon (TOC) for the time interval June 2003-Feb 2010. Flux ranges of studied parameters are (i) total diatoms = 1.2 _* 108-4.7 _* 104 valves m-2 d-1 (average = 5.9 exttimes 106 valves ± 1.4 exttimes 107); (ii) BSi = 296-0.5 mg m-2 d-1 (average = 41.1 ± 53.5 mg m-2 d-1), and (iii) TOC = 97-1 mg m-2 d-1 (average = 20.5 ± 17.8 mg m-2 d-1). Throughout the experiment, the overall good match of total diatom, BSi and TOC fluxes is reasonably consistent and reflects well the temporal occurrence of the main Mauritanian upwelling season. Spring and summer are the most favorable seasons for diatom pro- duction and sedimentation: out of the recorded 14 diatom maxima of different magnitude, six occurred in spring and four in summer. The diverse diatom community at site CBeu is composed of four main assemblages: benthic, coastal upwelling, coastal planktonic and open-ocean diatoms, reflecting different productivity conditions and water masses. A striking feature of the temporal variability of the diatom populations is the persistent pattern of seasonal groups extquotesingle contribution: benthic and coastal upwelling taxa dominated during the main upwelling season in spring, while open-ocean diatoms were more abundant in fall and winter, when the upper water column becomes stratified, upwelling relaxes and productivity decreases. The relative abundance of benthic diatoms strongly increased after 2006, yet their spring-summer contribution remained high until the end of the trap experiment. The occurrence of large populations of benthic diatoms at the hemipelagic CBeu site is interpreted to indicate transport from shallow waters via nepheloid layers. We argue that a significant amount of valves, BSi and TOC produced in waters overlying the Banc d extquotesingleArguin and the Mauritanian shelf is effectively transported to the CBeu trap in intermediate waters at the outer Mauritanian slope. The impact of the intermediate and bottom-near nepheloid layers-driven transport in the transfer of valves and bulk particulates and its potential contribution to the export of biogenic materials from the shelf and uppermost slope might play a significant role in hemipelagial fluxes off Mauritania.